Children and youth during the Civil War era - Marten, James Alan (Children and youth in America., 2012)
"The Civil War is a much plumbed area of scholarship, so much so that at times it seems there is no further work to be done in the field. However, the experience of children and youth during that tumultuous time remains a relatively unexplored facet of the conflict. Children and Youth during the Civil War Era seeks a deeper investigation into the historical record by and giving voice and context to their struggles and victories during this critical period in American history. Prominent historians and rising scholars explore issues important to both the Civil War era and to the history of children and youth, including the experience of orphans, drummer boys, and young soldiers on the front lines, and even the impact of the war on the games children played in this collection. Each essay places the history of children and youth in the context of the sectional conflict, while in turn shedding new light on the sectional conflict by viewing it through the lens of children and youth. A much needed, multi-faceted historical account, Children and Youth during the Civil War Era touches on some of the most important historiographical issues with which historians of children and youth and of the Civil War home front have grappled over the last few years"--